ANALYSIS OF COVID-19 FOMITE TRANSMISSION MODEL WITH DISINFECTANT SPRAY - Sabran, La Ode; Rianjaya, Ilham Dangu; Hasibuan, Lilis Harianti; Nashar, La Ode (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
The SARS-CoV-2 virus causes the infectious disease COVID-19. This virus can be transmitted via the fomite mode of transmission (the surface of objects contaminated with the virus). It is possible to prevent the spread of COVID-19 by spraying disinfectant on infected objects. This research aims to develop a mathematical model of COVID-19 fomite transmission with disinfectant spraying intervention. The model was analyzed by determining its stability and critical point. A Ro analysis was conducted to determine the impact of disinfectant spraying on the eradication or spread of the disease. The results demonstrated that, in the absence of disinfectant spraying, the number of infected humans increased rapidly and abruptly. Based on the findings of sensitivity analysis, it is known that spraying disinfectants is highly effective at reducing Ro, thereby reducing the number of infected humans and eradicating the disease from the population. In this study, the recommended measure to prevent the spread of COVID-19 is the periodic application of disinfectant in accordance with medical regulations.